The shift towards democratic governance: System change versus regime change analysis in The Gambia 2017-2019 - Sunkung Danso; Sulikah Asmorowati (Faculty of Social and Political Science, Universitas Airlangga, 2020)
Democratic governance has been seen as a catalyst for inclusive growth and meaningful development in many countries. Shifting from authoritarian rule to more democratic rule has also been seen as essential for many governments worldwide. Democratic governance is often a problem for developing countries, including most African countries and particularly The Gambia. This paper analyses the shift towards a more democratic governance style that is heated debated in The Gambia. The debate started when one of the coalition government members asserted that they could achieve regime change; however, a democratic system change remains lacking. This paper has sought to analyze whether the shift toward a more democratic leadership style in The Gambia is one of system change or regime change and ascertain what has democratically changed and bad governance in the new government. This article’s main objective is to create political awareness and enlighten the readers on the change’s misconceptions towards democratic governance. The discussion focuses on democratic governance and the collective action theory of governance to explain the democratic process in New Gambia. This study adopts qualitative case study research methods; the research employed a systematic review of the existing scholarly journal articles, books, newspapers, and television interview recordings. The observation used to identify, understand, and interpret the democratic governance situation in The Gambia from 2017 to 2019. The findings show that the coalition government has succeeded in achieving a democratic regime change; however, the democratic system change itself is too slow, or it is not happening. For the first time in The Gambia’s history, a seating president defeat through the ballot box. In conclusion, the democratic governance system change is far-fetched. It is vital to state that there is little or no difference between Jammeh’s regime and the current regime under President Barrow’s leadership. The same problems continue to persist. Finally, the transparency and accountability mechanisms must be enhanced to address the endemic problem of corruption.